Exercise performance and physiological responses: the potential role of redox imbalance. Issue 7 (31st March 2017) - Vidal, Kavey; Robinson, Nathaniel; Ives, Stephen J.
Abstract: Increases in oxidative stress or decreases in antioxidant capacity, or redox imbalance, are known to alter physiological function and has been suggested to influence performance. To date, no study has sought to manipulate this balance in the same participants and observe the impact on physiological function and performance. Using a single‐blind, placebo‐controlled, and counterbalanced design, this study examined the effects of increasing free radicals, via hyperoxic exposure (Fi O2  = 1.0), and/or increasing antioxidant capacity, through consuming an antioxidant cocktail (AOC; vitamin‐C, vitamin‐E, α ‐lipoic acid), on 5‐kilometer (km) cycling time‐trial performance, and the physiological and fatigue responses in healthy college‐aged males. Hyperoxic exposure prior to the 5 km TT had no effect on performance, fatigue, or the physiological responses to exercise. The AOC significantly reduced average power output (222 ± 11 vs. 214 ± 12 W), increased 5 km time (516 ± 17 vs. 533 ± 18 sec), suppressed ventilation ( V E ; 116 ± 5 vs. 109 ± 13 L/min), despite similar oxygen consumption ( V O2 ; 43.1 ± 0.8 vs. 44.9 ± 0.2 mL/kg per min), decreased V E / V O2 (35.9 ± 2.0 vs. 32.3 ± 1.5 L/min), reduced economy ( V O2 /W; 0.20 ± 0.01 vs. 0.22 ± 0.01), increased blood lactate (10 ± 0.7 vs. 11 ± 0.7 mmol), and perception of fatigue (RPE; 7.39 ± 0.4 vs. 7.60 ± 0.3) at the end of the TT, as compared to placebo (main effect, placebo vs. AOC, respectively). Our data demonstrate that prior to exercise, ingesting an AOC, but not exposure to hyperoxia, likely disrupts the delicate balance between pro‐ and antioxidant forces, which negatively impacts ventilation, blood lactate, economy, perception of fatigue, and performance (power output and 5 km time) in young healthy males. Thus, caution is warranted in athletes taking excess exogenous antioxidants. Abstract : Our data demonstrate that prior to exercise, ingesting an antioxidant cocktail, but not exposure to hyperoxia, likely disrupts the delicate balance between pro‐ and antioxidant forces, which negatively impacts ventilation, blood lactate, economy, perception of fatigue, and performance (power output and 5 km time) in young healthy males. Thus, caution is warranted in athletes taking excess exogenous antioxidants.